Impact of inflation on economic growth in srilanka - Gowshiga, S.; Mitharshana, S. (university of Jaffna, 2014)
This paper attempt to examine main impact of Inflation on Economic growth in SriLanka over the period of 1990-2012. One of the Sri Lanka's central bank objective of micro economic policies is to promote economic growth and price stability(inflation)however there has been controversial debate on whether inflation on promotes or harms economic growth. Based on this debate this study examines the impact of inflation on economic growth in Sri Lanka. This research examines some variables such as Colombo Consumer Price Index (CCPI) was used as a proxy for inflation and the GDP & GNP as a perfect proxy for economic growth to examine the relationship. The study considers the independent variable is inflation (CCPI)and dependent variables are economic growth (GDP & GNP)and the data are mainly collected from economic and social statistics of Sri Lanka. Correlation and co efficient technique, regression curve fit, compare the inflation and economic growth by using line diagram method establish the relationship between money and economic growth. Monetary policy practitioners are of the view that inflation is detrimental to economic growth while structuralizes believe that moderate inflation can contribute to economic growth. Finally research suggests that inflation has a negative impact on economic growth in Sri Lanka. The research also established that there was no more correlation between inflation and economic growth during the period of study in Sri Lanka.
Keywords: Inflation; Economic growth; Price stability; Srilanka; Core inflation